2021
DOI: 10.35848/1347-4065/abe996
|View full text |Cite
|
Sign up to set email alerts
|

Crystallite size analysis of Al/Ni multilayer powder by synchrotron radiation X-ray diffraction

Abstract: The self-propagated exothermic reaction characteristics of Al/Ni multilayer powders can be employed as heat sources and controlled by cold-rolling conditions. This feature depends on the heat propagation inside of crystal grains. Therefore, the crystallographic factor that relates cold-rolling conditions to exothermic characteristics should be identified. To determine the change trend in crystallite size with the increase in the number of rolling passes, the crystallite sizes in the Al/Ni multilayer powder wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The fwhm value of the (111) plane belonging to Cu-R and Cu−F is 0.253 and 0.188°, respectively. Because the crystallite sizes are inversely proportional to the fwhm value, 27 their crystallite sizes are estimated to be 33.8 and 45.5 nm, respectively, according to Scherrer's equation. The decrease in reflectance always relates to the increase in surface roughness.…”
Section: Resultsmentioning
confidence: 99%
“…The fwhm value of the (111) plane belonging to Cu-R and Cu−F is 0.253 and 0.188°, respectively. Because the crystallite sizes are inversely proportional to the fwhm value, 27 their crystallite sizes are estimated to be 33.8 and 45.5 nm, respectively, according to Scherrer's equation. The decrease in reflectance always relates to the increase in surface roughness.…”
Section: Resultsmentioning
confidence: 99%
“…However, because the free electron is a heat propagation carrier, we assumed that the heat propagation was disturbed by a decrease in the movability of this free electron with an increase in the number of crystallite boundaries due to thinning and multilayering. 28) Therefore, we concluded that the cold-rolling process has both a positive effect that causes an increase in the maximum exothermic temperature and a negative effect that causes a decrease in heat propagation. If the crystallite size of the Al/Ni powder, which is sufficiently multilayered by cold rolling, could be increased by other methods such as heat treatment, further improvement in the exothermic reaction characteristics could be expected.…”
Section: Introductionmentioning
confidence: 84%
“…In our study, to improve the productivity and convenience of the heat source, an Al/Ni multilayer powder fabricated by the coldrolling and frictional pulverizing methods was developed, and the thermal reaction characteristics were studied. 13,[25][26][27][28] In a previous study, we revealed that the exothermic reaction characteristics, such as the reaction speed and maximum exothermic reaction temperature, increase with an increase in the number of cold-rolling passes. 25) These characteristics can be controlled to some extent by changing the rolling conditions.…”
Section: Introductionmentioning
confidence: 99%